Investigating the function of prehistoric stone bowls and griddle stones in the Aleutian Islands by lipid residue analysis. Issue 3 (4th June 2018) - Admiraal, Marjolein; Lucquin, Alexandre; von Tersch, Matthew; Jordan, Peter D.; Craig, Oliver E.
Abstract: The earliest durable cooking technologies found in Alaska are stone bowls and griddle stones recovered from the Aleutian Islands. This article aims to identify the function of these artefacts. Molecular and chemical analyses of carbonised residues found on their surfaces confirm that these artefacts were used to process marine resources. Both artefacts have high lipid content and C:N ratios, suggesting they were used to process oily substances. Stable isotope results of individual lipids suggest that they were used to process different sets of resources within the aquatic spectrum as griddle stones have slightly more 13 C-depleted lipids than stone bowls, possibly indicating more variable use. Integration of these results with archaeological and ethnographic data leads us to infer that griddle stones were used for cooking a diversity of aquatic resources, possibly with the addition of plant foods, whereas stone bowls were specifically used to render marine mammal fats. We further hypothesize that a sudden peak in stone bowl frequencies at 4000–3000 cal yr BP was connected to a Neoglacial cold spell bringing sea ice conditions to the Aleutian Islands. This may have led to new subsistence strategies in which the rendering of marine mammal fats played a central role.